2012
DOI: 10.1029/2012tc003155
|View full text |Cite
|
Sign up to set email alerts
|

Variable shortening rates in the eastern Himalayan thrust belt, Bhutan: Insights from multiple thermochronologic and geochronologic data sets tied to kinematic reconstructions

Abstract: We present data on the burial, displacement and exhumation history of the Himalayan fold‐thrust belt in eastern Bhutan. These data document the magnitude and timing of displacement of large, discrete structures and highlight temporal variability in shortening rates. Eight new40Ar/39Ar ages from white mica, 32 new zircon (U‐Th)/He ages, 7 new apatite fission track ages, and 1 new U‐Pb zircon (LA‐MC‐ICP‐MS) metamorphic rim growth age are combined with published cooling ages and deformation temperatures, and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
173
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 89 publications
(182 citation statements)
references
References 106 publications
(237 reference statements)
9
173
0
Order By: Relevance
“…In addition to residence time and thermal conditions experienced by the rocks affecting argon loss, they suggested that a ±2 Ma age dispersion would be expected due to diffusive differences caused by grain size variations. MAr ages from eastern Bhutan postdate the age of south-directed shear on the MCT in this region (Stüwe and Foster, 2001;Grujic et al, 2002;Daniel et al, 2003;Kellett et al, 2009;Long et al, 2012). Thus, we interpret the age range of these four MAr samples as the window of permissible exhumation-induced cooling through the modeled closure temperatures of white mica (Ehlers, 2005;Braun, 2003).…”
Section: Thermochronologic Datamentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to residence time and thermal conditions experienced by the rocks affecting argon loss, they suggested that a ±2 Ma age dispersion would be expected due to diffusive differences caused by grain size variations. MAr ages from eastern Bhutan postdate the age of south-directed shear on the MCT in this region (Stüwe and Foster, 2001;Grujic et al, 2002;Daniel et al, 2003;Kellett et al, 2009;Long et al, 2012). Thus, we interpret the age range of these four MAr samples as the window of permissible exhumation-induced cooling through the modeled closure temperatures of white mica (Ehlers, 2005;Braun, 2003).…”
Section: Thermochronologic Datamentioning
confidence: 99%
“…North of the MCT, ZHe cooling ages are limited to two samples, one from the structurally higher Greater Himalaya and one from Tethyan rocks at the western edge of the Sakteng Klippe. These samples recorded cooling ages of 7.4 ± 1.6 and 7.1 ± 0.3 Ma, respectively (Coutand et al, 2014;Long et al, 2012).…”
Section: Thermochronologic Datamentioning
confidence: 99%
See 3 more Smart Citations